Emotional Intelligence and job performance: Evidence from railroad industry - Masoumeh Bahmanabadi; Mostafa Jafari (Management Science Letters)
This paper presents an empirical investigation to study the relationship between emotional intelligence and job performance in railroad industry. The study uses two questionnaires, one for measuring emotional intelligence adopted from Salovey and Mayer (1989) [Salovey, P., & Mayer, J. D. (1989). Emotional intelligence. Imagination, Cognition and Personality, 9(3), 185-211.] and the other one for measuring job performance. The study selects 300 full time employees who work for railroad industry in city of Tehran, Iran, distributes two questionnaires among the employees and managed to collect all filled ones. Using Spearman correlation, the study has determined a positive and meaningful relationship between emotional intelligence and job performance (r = 0.796, Sig. = 0.000). In addition, there were positive and meaningful relationships between four components of emotional intelligence, namely consciousness (r = 0.642, Sig. = 0.000), self-regulation (r = 0.41, Sig. = 0.000), self-awareness ( r = 0.552, Sig. = 0.000) and social skills (r = 0.524, Sig. = 0.000).